Recombinant human thrombopoietin improves hematopoietic stem cell differentiation and T-cell immune homeostasis in patients with severe aplastic anemia by upregulating c-MPL - Deng, Ling; Liu, Chenchen; Guo, Yiyu; Liu, Chunyan; Fu, Rong (Frontiers in Pharmacology, 2025)
BackgroundRecombinant human thrombopoietin (rhTPO) regulates platelet production by promoting megakaryocyte proliferation and has shown promising therapeutic effects in hematopoietic recovery for severe aplastic anemia (SAA). However, its potential impact on immune cells remains unclear.MethodsThis study included 23 patients with SAA, who were divided into two groups based on whether they received rhTPO. Flow cytometry was used to assess the proportions of peripheral immune cells and hematopoietic stem cells (HSCs), as well as their c-MPL expression. Further validation was performed by in vitro culture experiments and SAA mice.ResultsThe rhTPO group exhibited an upward trend in platelet counts (PLT), as well as a higher proportion of peripheral CD4+ T cells and an increased CD4+/CD8+ T cell ratio. The expression of the receptor of rhTPO, c-MPL, was significantly increased on CD4+ T cells and regulatory T cells (Tregs). More important is we found c-MPL expression on bone marrow CD34+ cells was unregulated in the rhTPO group. In vitro stimulation of bone marrow mononuclear cells from patients with SAA using rhTPO elevated the proportion of Tregs and the CD4+/CD8+ T cell ratio. Furthermore, CsA combined with rhTPO treatment in SAA mice significantly restored the proportion of peripheral Tregs.ConclusionrhTPO can induce the upregulation of c-MPL expression on HSCs, CD4+ T cells, and Tregs in patients with SAA. It accelerates platelet production and regulates the proliferation of CD4+ T cells and Tregs, thereby promoting immune homeostasis restoration in SAA.